2005
DOI: 10.1021/jp0580423
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the HCCO + NO2 Reaction

Abstract: The kinetics of the HCCO + NO2 reaction were investigated using a laser photolysis/infrared diode laser absorption technique. Ethyl ethynyl ether (C2H5OCCH) was used as the HCCO radical precursor. Transient infrared detection of the HCCO radical was used to determine a total rate constant fit to the following expression: k1= (2.43 +/- 0.26) x 10(-11) exp[(171.1 +/- 36.9)/T] cm3 molecule(-1) s(-1) over the temperature range of 298-423 K. Transient infrared detection of CO, CO2, and HCNO products was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…This radical may be a key intermediate in the combustion of sulfur-containing fuels and may play an important role in the RAPRENO x (rapid reduction of nitrogen oxides) process. , There have been numerous reports on theoretical and experimental approaches to eliminate NO, many of which contain cyanogen species as an effective reagent to remove NO. Our purpose of this study is to find the possible reactants which may react with NO to form the stable product such as N 2 , which is not harmful to our environment and possibly with lower energy barriers.…”
Section: Introductionmentioning
confidence: 99%
“…This radical may be a key intermediate in the combustion of sulfur-containing fuels and may play an important role in the RAPRENO x (rapid reduction of nitrogen oxides) process. , There have been numerous reports on theoretical and experimental approaches to eliminate NO, many of which contain cyanogen species as an effective reagent to remove NO. Our purpose of this study is to find the possible reactants which may react with NO to form the stable product such as N 2 , which is not harmful to our environment and possibly with lower energy barriers.…”
Section: Introductionmentioning
confidence: 99%
“…An even cleaner, and perhaps more promising HCCO source than ketene is the photo-dissociation at 193 nm of ethyl ethynyl ether, [33][34][35] as recently employed by Meyer and Hershberger in their study of the HCCO + NO 2 reaction, in which HCCO was monitored by transient infrared absorption. 36…”
Section: Mass Spectrometric and Infrared Detection Methodsmentioning
confidence: 99%
“…However, subsequent studies reported that the HCCO + H formation process 3a is a minor product channel (<20%) of reaction 3. The main product channel (>60%) is CH 2 ( 3 B 1 and 1 A 1 ) + CO, processes 3b and 3c. Subsequently, the photodissociation of ethyl ethynyl ether (EEE, C 2 H 5 OCCH) at 193 nm has been employed , as an even cleaner HCCO source than ketene. …”
Section: Introductionmentioning
confidence: 99%
“…20−22 The main product channel (>60%) is CH 2 ( 3 B 1 and 1 A 1 ) + CO, processes 3b and 3c. Subsequently, the photodissociation of ethyl ethynyl ether (EEE, C 2 H 5 OC CH) at 193 nm has been employed 10,23 as an even cleaner HCCO source than ketene.…”
Section: Introductionmentioning
confidence: 99%